The Translation of Sports News Publicity from the Perspective of Psychological Cognition - Yidan Wang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The purpose was to explore the translation of sports news publicity from a psychological cognitive perspective. Describe the model of translation process from the perspective of cognitive psychology, apply this model to explain the phenomenon of the objective world, that is, the process of translation, and make an empirical study of the process of translation understanding using the method of thinking aloud in cognitive psychology. The first group is 12.65 and the second group is only 1.21. In addition, there is also a large difference in the use of research strategies, which is 3.95 in the first group and 23.26 in the second group, which indicates that the subjects can find certain words and sentences in the language of knowledge when using these strategies, the knowledge and ignorance stored in long memory are different, - and this also shows that the first group of subjects will again understand more and make the surface information of the original text. The translation process model from the perspective of cognitive psychology allows researchers to understand the translator's translation psychology from another perspective, which has certain significance for people to understand the translator's psychology during the translation process. The tailoring translations to cognitive processes can boost emotional resonance and brand loyalty. Moreover, employing cognitive linguistic strategies improves message retention and fosters a deeper connection with the sports audience. Also, understanding cultural nuances ensures accurate communication of sports news and maximizes global outreach.